Grain of Hybrids Between Spelt ( Triticum spelta L.) and Bread Wheat ( Triticum aestivum L.) as a New Raw Material for Breadmaking - Marian Wiwart; Anna Szafrańska; Elżbieta Suchowilska (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to determine differences in the technological quality of grain of hybrids between spelt ( Triticum spelta ) and bread wheat ( T. aestivum ) as compared with the grain of their parental forms, i.e., modern bread wheat cultivars and spelt breeding lines. The content of basic nutrients in grain, milling quality of grain, rheological properties of dough, and bread quality were evaluated. Grain yields were around 18% lower in hybrid lines than in bread wheat. Gluten content was significantly higher in the grain of hybrid lines (34.0 vs . 27.5 g/100 g), and it did not differ significantly from that noted in spelt grain (36.1 g/100 g). The gluten index did not differ significantly between hybrid lines and bread wheat cultivars (77 vs . 85), and it was significantly higher than in spelt (43). Protein content was significantly higher in the flour obtained from hybrid lines than from bread wheat. Analyzed dough parameters in hybrid lines assumed intermediate values relative to parental forms, and protein parameters had a stronger discriminatory power than starch parameters. Bread made from the grain of single-cross hybrids between spelt and bread wheat was characterized by high quality and in many cases superior attributes relative to bread made from spelt flour. The study demonstrated that hybrids between T. spelta and T. aestivum can become a new, valuable source of grain for bread production.